Data and computer communications - Stallings, William (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2007)
"Data and Computer Communications, Eighth Edition offers a clear, comprehensive, and unified view of the entire fields of data communications, networking, and protocols. William Stallings organizes this massive subject into small, comprehensible elements, building a complete survey of the state-of-the-art, one piece at a time. Stallings has substantially revised this international best-seller to reflect today's latest innovations, from WiFi and 10 Gbps Ethernet to advanced congestion control and IP performance metrics."--BOOK JACKET.
Includes bibliographical references (p. 847-857) and index.
Keywords: Data transmission systems; Computer networks